Increasing Number of Women on Supervisory Boards of Major Companies in Germany: Executive Boards Still Dominated by Men - Elke Holst; Katharina Wrohlich (DIW Weekly Report, 2019)
The gender quota for supervisory boards is continuing to show its impact: the proportion of women on the supervisory boards of the 200 highest-performing companies in Germany increased by over two percentage points to 27 percent the past year. In the 100 largest companies, it increased by over three percentage points to 28 percent. However, there are now indications that the companies are only doing the bare minimum, as the proportion of women in the group of the 30 largest DAX companies-many of which have already reached the minimum of 30 percent women-has stagnated at one-third. Additionally, it is becoming more and more apparent that the gender quota does not have the impact hoped for on executive boards, at least not in the short term. Even though the ten percent mark was reached for the first time in the top 100 companies, most development is still taking place at a snail's pace. It is still up to companies to stymie demands for binding board member quotas. To do this, however, they must act as quickly as possible and consistently fill all hierarchical levels, especially beneath the board, with more women in order to increase the pool of potential female board members.
Keywords: D22; J16; J59; J78; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women